Occupational interventions and their effects on work-related and mental health outcomes: A scoping review protocol - Behdin Nowrouzi-Kia; Hong Ki Chloe Lau; Sana Siddiqui; Raihana Premji; Grant Hamblin; Armaan Rehman Shah; R. Nicholas Carleton (PLoS ONE, 2026)
Background The well-being of individuals within their workplace (i.e., workplace mental health) has important implications for their productivity and mental health. The extensive literature on the effectiveness of individual workplace interventions does not yet include a comprehensive synthesis of occupational interventions delivered in workplace settings. Objective The proposed scoping review is designed to identify and categorize occupational interventions studied in the literature; and 2) map reported effects on work-related outcomes and mental health outcomes. Methods The review will examine five online databases to identify relevant articles: Embase, CINAHL, APA PsycINFO, MEDLINE, and Web of Science. The inclusion criteria will encompass peer-reviewed English-language studies published from 2005 to 2025, focusing on the effects of occupational interventions designed to improve workplace mental health. The results will support work participation among working adults. Discussion The review will examine the effects of current occupational interventions on workers’ mental health and well-being, as well as on work-related outcomes (e.g., work participation, productivity). The review results can inform researchers designing future studies assessing the effectiveness of occupational interventions on mental health and guide the development of new interventions.